Characterization of contrast-mediated collinear interactions in the human visual system - Luca Battaglini; Giulio Contemori; Gianluca Campana; Marco Bertamini; Gianluca Ruffato; Marcello Maniglia (Scientific Reports)
Abstract Collinear modulation represents a fundamental building block of our perceptual world, and its study has enhanced our understanding of contrast sensitivity, spatial integration, and neural plasticity in the visual system. In this phenomenon, the visibility of a target is influenced by collinear elements. Four key factors modulate this effect: the distance between target and flankers, the contrast of the flankers, retinal eccentricity, and spatial frequency. Each of these elements affects collinear modulation, increasing or reducing the target’s visibility. Short target-to-flankers separations decrease contrast sensitivity, while larger separations increase it. However, this pattern holds for high contrast flankers, whereas low contrast flankers increase contrast sensitivity at short separations, while the effect is weaker or absent at large separations. Moreover, eccentricity appears to increase the spatial extent of inhibition. Across three experiments, we systematically varied these key factors. In Experiments 1 and 2, we manipulated spatial frequency, flankers’ separation, and flankers’ contrast in foveal vision. In Experiment 3, we varied flankers’ separation and flankers’ contrast in peripheral vision. The results reveal a complex pattern that may help reconcile previously conflicting findings in both healthy participants and clinical populations, offering an updated framework for the study of neural plasticity in the visual system.